10問 足し算 分数足し算 数学・算数の教材公開ページ

20 

Loading....

Loading....

Loading....

Loading....

Loading....

全文

(1)

(1) 24 5 + 5

2

3 = (2) 3

1 3 + 2

5 6 =

(3) 23 5 + 3

2

3 = (4) 2

1 6 + 1

1 3 =

(5) 51 2 + 4

1

3 = (6) 4

1 2 + 1

1 4 =

(7) 31 4 + 3

1

6 = (8) 1

3 4 + 2

3 5 =

(9) 22 3 + 1

1

6 = (10) 1

5 6 + 1

(2)

(1) 24 5 + 5

2

3 =

8

7

15

(2) 3

1 3 + 2

5

6 =

6

1

6

(3) 23 5 + 3

2

3 =

6

4

15

(4) 2

1 6 + 1

1

3 =

3

1

2

(5) 51 2 + 4

1

3 =

9

5

6

(6) 4

1 2 + 1

1

4 =

5

3

4

(7) 31 4 + 3

1

6 =

6

5

12

(8) 1

3 4 + 2

3

5 =

4

7

20

(9) 22 3 + 1

1

6 =

3

5

6

(10) 1

5 6 + 1

1

2 =

3

1

(3)

(1) 35 6 + 1

1

2 = (2) 1

1 3 + 2

1 2 =

(3) 31 2 + 3

5

6 = (4) 3

3 4 + 5

5 6 =

(5) 31 4 + 2

1

3 = (6) 4

1 3 + 4

5 6 =

(7) 34 + 4 1

2 = (8)

1 6 + 1

1 4 =

(9) 14 5 + 2

1

2 = (10) 2

1 4 + 1

(4)

(1) 35 6 + 1

1

2 =

5

1

3

(2) 1

1 3 + 2

1

2 =

3

5

6

(3) 31 2 + 3

5

6 =

7

1

3

(4) 3

3 4 + 5

5

6 =

9

7

12

(5) 31 4 + 2

1

3 =

5

7

12

(6) 4

1 3 + 4

5

6 =

9

1

6

(7) 34 + 4 1 2 =

5

1

4

(8)

1 6 + 1

1

4 =

1

5

12

(9) 14 5 + 2

1

2 =

4

3

10

(10) 2

1 4 + 1

1

6 =

3

5

(5)

(1) 11 3 + 2

1

2 = (2) 2

1 2 + 5

2 3 =

(3) 42 3 + 2

5

6 = (4) 3

1 2 + 5

3 4 =

(5) 12 3 + 1

5

6 = (6) 4

1 2 + 3

1 6 =

(7) 14 + 1 5

6 = (8) 3

2 3 + 4

1 4 =

(9) 35 6 + 4

1

3 = (10) 1

2 3 + 1

(6)

(1) 11 3 + 2

1

2 =

3

5

6

(2) 2

1 2 + 5

2

3 =

8

1

6

(3) 42 3 + 2

5

6 =

7

1

2

(4) 3

1 2 + 5

3

4 =

9

1

4

(5) 12 3 + 1

5

6 =

3

1

2

(6) 4

1 2 + 3

1

6 =

7

2

3

(7) 14 + 1 5 6 =

2

1

12

(8) 3

2 3 + 4

1

4 =

7

11

12

(9) 35 6 + 4

1

3 =

8

1

6

(10) 1

2 3 + 1

1

4 =

2

11

(7)

(1) 31 2 + 1

2

5 = (2) 2

1 3 + 1

5 6 =

(3) 35 6 + 4

2

3 = (4) 3

2 3 + 3

1 6 =

(5) 11 3 + 1

5

6 = (6)

1 6 + 2

1 3 =

(7) 31 4 + 3

1

6 = (8) 2

1 6 + 4

1 2 =

(9) 11 4 + 3

1

2 = (10) 1

2 3 + 1

(8)

(1) 31 2 + 1

2

5 =

4

9

10

(2) 2

1 3 + 1

5

6 =

4

1

6

(3) 35 6 + 4

2

3 =

8

1

2

(4) 3

2 3 + 3

1

6 =

6

5

6

(5) 11 3 + 1

5

6 =

3

1

6

(6)

1 6 + 2

1

3 =

2

1

2

(7) 31 4 + 3

1

6 =

6

5

12

(8) 2

1 6 + 4

1

2 =

6

2

3

(9) 11 4 + 3

1

2 =

4

3

4

(10) 1

2 3 + 1

5

6 =

3

1

(9)

(1) 21 2 + 1

1

6 = (2) 3

1 6 + 5

3 4 =

(3) 41 4 + 2

5

6 = (4) 2

1 3 +

5 6 =

(5) 11 6 + 5

1

3 = (6) 2

1 3 + 1

5 6 =

(7) 22 3 + 1

1

2 = (8) 6

1 2 + 1

5 6 =

(9) 13 4 + 1

1

3 = (10) 4

1 6 + 4

(10)

(1) 21 2 + 1

1

6 =

3

2

3

(2) 3

1 6 + 5

3

4 =

8

11

12

(3) 41 4 + 2

5

6 =

7

1

12

(4) 2

1 3 +

5

6 =

3

1

6

(5) 11 6 + 5

1

3 =

6

1

2

(6) 2

1 3 + 1

5

6 =

4

1

6

(7) 22 3 + 1

1

2 =

4

1

6

(8) 6

1 2 + 1

5

6 =

8

1

3

(9) 13 4 + 1

1

3 =

3

1

12

(10) 4

1 6 + 4

2

3 =

8

5

(11)

(1) 11 6 +

1

2 = (2) 1

1 2 + 1

3 5 =

(3) 51 5 + 3

1

3 = (4)

4 5 + 5

1 2 =

(5) 11 5 + 4

1

2 = (6) 2

3 4 + 2

1 6 =

(7) 21 5 + 2

3

4 = (8) 2

2 3 + 2

1 2 =

(9) 11 4 + 1

1

2 = (10) 2

5 6 + 2

(12)

(1) 11 6 +

1 2 =

1

2

3

(2) 1

1 2 + 1

3

5 =

3

1

10

(3) 51 5 + 3

1

3 =

8

8

15

(4)

4 5 + 5

1

2 =

6

3

10

(5) 11 5 + 4

1

2 =

5

7

10

(6) 2

3 4 + 2

1

6 =

4

11

12

(7) 21 5 + 2

3

4 =

4

19

20

(8) 2

2 3 + 2

1

2 =

5

1

6

(9) 11 4 + 1

1

2 =

2

3

4

(10) 2

5 6 + 2

1

3 =

5

1

(13)

(1) 51 3 + 4

4

5 = (2)

1 2 + 1

2 5 =

(3) 23 + 1 1

6 = (4) 3

5 6 + 2

1 3 =

(5) 41 2 + 5

1

3 = (6) 1

1 2 + 2

3 4 =

(7) 15 6 + 2

1

3 = (8) 1

2 3 + 2

5 6 =

(9) 31 6 + 2

1

3 = (10) 4

1 4 + 1

(14)

(1) 51 3 + 4

4

5 =

10

2

15

(2)

1 2 + 1

2

5 =

1

9

10

(3) 2

3 + 1 1 6 =

1

5

6

(4) 3

5 6 + 2

1

3 =

6

1

6

(5) 41 2 + 5

1

3 =

9

5

6

(6) 1

1 2 + 2

3

4 =

4

1

4

(7) 15 6 + 2

1

3 =

4

1

6

(8) 1

2 3 + 2

5

6 =

4

1

2

(9) 31 6 + 2

1

3 =

5

1

2

(10) 4

1 4 + 1

1

2 =

5

3

(15)

(1) 31 2 + 1

1

6 = (2) 3

1 3 + 2

3 5 =

(3) 31 2 + 2

1

6 = (4) 1

1 2 + 3

1 5 =

(5) 11 2 + 2

5

6 = (6)

3 5 + 1

1 4 =

(7) 21 6 + 1

1

3 = (8) 4

1 6 + 5

1 2 =

(9) 51 3 + 1

1

6 = (10) 5

3 4 + 5

(16)

(1) 31 2 + 1

1

6 =

4

2

3

(2) 3

1 3 + 2

3

5 =

5

14

15

(3) 31 2 + 2

1

6 =

5

2

3

(4) 1

1 2 + 3

1

5 =

4

7

10

(5) 11 2 + 2

5

6 =

4

1

3

(6)

3 5 + 1

1

4 =

1

17

20

(7) 21 6 + 1

1

3 =

3

1

2

(8) 4

1 6 + 5

1

2 =

9

2

3

(9) 51 3 + 1

1

6 =

6

1

2

(10) 5

3 4 + 5

1

2 =

11

1

(17)

(1) 11 6 + 2

1

2 = (2) 4

1 6 + 4

1 3 =

(3) 16 + 1 2

3 = (4) 5

1 2 + 2

3 4 =

(5) 11 3 + 3

5

6 = (6) 3

1 6 + 4

1 4 =

(7) 34 + 4 1

2 = (8) 2

2 3 + 5

5 6 =

(9) 11 2 +

1

6 = (10) 3

1 2 + 3

(18)

(1) 11 6 + 2

1

2 =

3

2

3

(2) 4

1 6 + 4

1

3 =

8

1

2

(3) 1

6 + 1 2 3 =

1

5

6

(4) 5

1 2 + 2

3

4 =

8

1

4

(5) 11 3 + 3

5

6 =

5

1

6

(6) 3

1 6 + 4

1

4 =

7

5

12

(7) 34 + 4 1 2 =

5

1

4

(8) 2

2 3 + 5

5

6 =

8

1

2

(9) 11 2 +

1 6 =

1

2

3

(10) 3

1 2 + 3

3

4 =

7

1

(19)

(1) 21 2 + 4

1

4 = (2) 2

1 3 + 1

1 6 =

(3) 35 6 + 5

2

3 = (4) 1

1 2 + 3

2 5 =

(5) 11 6 + 1

1

3 = (6) 3

1 2 + 2

1 4 =

(7) 31 2 + 1

3

4 = (8)

3 4 + 1

1 2 =

(9) 13 4 + 2

1

5 = (10) 3

3 4 +

(20)

(1) 21 2 + 4

1

4 =

6

3

4

(2) 2

1 3 + 1

1

6 =

3

1

2

(3) 35 6 + 5

2

3 =

9

1

2

(4) 1

1 2 + 3

2

5 =

4

9

10

(5) 11 6 + 1

1

3 =

2

1

2

(6) 3

1 2 + 2

1

4 =

5

3

4

(7) 31 2 + 1

3

4 =

5

1

4

(8)

3 4 + 1

1

2 =

2

1

4

(9) 13 4 + 2

1

5 =

3

19

20

(10) 3

3 4 +

1

2 =

4

1

Updating...

参照

Updating...

関連した話題 :